The wretched of France : the 1983 March for Equality and against Racism - Hajjat, Abdellali (Public cultures of the Middle East and North Africa., 2022)
"In 1983--as France struggled with race-based crimes, police brutality, and public unrest--youths from Vénissieux (working-class suburbs of Lyon) led the March for Equality and Against Racism, the first national demonstration of its type in France. As Abdellali Hajjat reveals, the historic March for Equality and Against Racism symbolized for many the experience of the children of postcolonial immigrants. Inspired by the May '68 protests, these young immigrants stood against racist crimes, for equality before the law and the police, and for basic rights such as the right to work and housing. Hajjat also considers the divisions that arose from the march and offers fresh insight into the paradoxes and intricacies of movements pushing toward sweeping social change. Translated into English for the first time, The Wretched of France contemplates the protest's lasting significance in France as well as its impact within the context of larger and comparable movements for civil rights, particularly in the U.S."--